GANGGUAN REPRODUKSI SAPI PERAH DI UNIT PELAKSANA TEKNIS DINAS BALAI PENGEMBANGAN BIBIT PAKAN TERNAK DAN DIAGNOSTIK KEHEWANAN (UPTD BPBPTDK) YOGYAKARTA TAHUN 2009-2012 - , DIAN UNTARI ADE WULAN, drh. Surya Agus Prihatno, M.P ([Yogyakarta] : Universitas Gadjah Mada, 2013)
One of fieldwork practices or Praktek Kerja Lapangan (PKL) was conducted in Unit Pelaksana Teknis Dinas Balai Pengembangan Bibit Pakan Ternak dan Diagnostik Kehewanan (UPTD BPBPTDK), Yogyakarta's department of Agriculture to fulfill the practice fieldwork assignment which was scheduled. It was also conducted to gather data for the final paper. This final paper was aimed to see the number of reproduction disorders in dairy cows at UPTD BPBPTDK Yogyakarta in 2009-2012. The data were collected through interviews and direct discussions with the farm managers. It was also collected based on the recording data of the reproduction cases which occurred in UPTD BPBPTDK Yogyakarta farm for 4 years. According to the data, the results showed that reproduction disorders percentace at uptd bpbptdk yogykarta in 2009 until 2012 were mastitis 17.3%, placental retention 5.4%, dystocia 4.8 %, metritis 3.6%, IBR 2.4%, repeat breeder 2.4%, and uterus prolaps 0.6%.